1999
DOI: 10.1093/genetics/153.3.1385
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Loss-of-Function Mutants in Xiphophorus Caused by Xmrk-Oncogene Deletion and Gene Disruption by a Transposable Element

Abstract: The overexpression of the Xmrk oncogene (ONC-Xmrk) in pigment cells of certain Xiphophorus hybrids has been found to be the primary change that results in the formation of malignant melanoma. Spontaneous mutant stocks have been isolated that have lost the ability to induce tumor formation when crossed with Xiphophorus helleri. Two of these loss-of-function mutants were analyzed for genetic defects in ONC-Xmrk's. In the lof-1 mutant a novel transposable element, TX-1, has jumped into ONC-Xmrk, leading to a disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The Xmrk gene is hypothesized to have arisen from gene duplication and nonhomologous recombination during evolution [5,22]. There are three Xiphophorus orthologs of the EGFR gene: egfra, which encodes a tyrosine kinase receptor; egfrb, which is a protooncogene form termed INV-Xmrk; and ONC-Xmrk, a duplicated version of INV-Xmrk, which is highly expressed in melanoma where it is responsible for inducing oncogenic transformation [23][24][25][26][27]. Oncogenic activation of the ONC-Xmrk receptor occurs via two mutations, i.e., G336R and C555S, both located in the extracellular domain that is not found in INV-Xmrk; these mutations result in constitutive receptor dimerization leading to constitutive kinase signaling [27,28].…”
Section: Genetic Characterization and Comparison Of Xmrk With The Human Egfrmentioning
confidence: 99%
“…The Xmrk gene is hypothesized to have arisen from gene duplication and nonhomologous recombination during evolution [5,22]. There are three Xiphophorus orthologs of the EGFR gene: egfra, which encodes a tyrosine kinase receptor; egfrb, which is a protooncogene form termed INV-Xmrk; and ONC-Xmrk, a duplicated version of INV-Xmrk, which is highly expressed in melanoma where it is responsible for inducing oncogenic transformation [23][24][25][26][27]. Oncogenic activation of the ONC-Xmrk receptor occurs via two mutations, i.e., G336R and C555S, both located in the extracellular domain that is not found in INV-Xmrk; these mutations result in constitutive receptor dimerization leading to constitutive kinase signaling [27,28].…”
Section: Genetic Characterization and Comparison Of Xmrk With The Human Egfrmentioning
confidence: 99%
“…Hybrids of different species within the genus Xiphophorus, pigmented platyfish (Xiphophorus maculatus) and non-pigmented swordtails (X. helleri), spontaneously develop melanoma. 45) The gene responsible was identified by analyzing the phenotype of this hybrid strain through genetic backcrossing, which resulted in the sequence of Xmrk (Xiphophorus melanoma receptor kinase), a novel receptor tyrosine kinase gene related to the epidermal growth factor receptor (EGFR), eventually being isolated. [46][47][48] To verify that a gene functions as an oncogene, it must be expressed in an organism.…”
Section: Melanoma Modelmentioning
confidence: 99%
“…Studies have demonstrated the gene disrupting effect of TE transposition in Xiphophorus [30], yet analyses of total TE numbers or specific TE sequences in different Xiphophorus hybrid tissues are missing. Due to their seemingly random insertion into the genome, the TE landscape can widely vary between different organisms.…”
Section: Introductionmentioning
confidence: 99%